ANALISIS GAYA KEPEMIMPINAN DALAM MENINGKATKAN DISIPLIN KERJA PADA KANTOR DISTRIK MANEKAR KABUPATEN TAMBRAUW PROVINSI PAPUA BARAT - Ratna Rosmauli Pakpahan; Arce Yulita Ferdinandus; Yusup Ajami (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
Leadership style is the way a leader is in the process of directing and influencing someone in order to achieve the agency's or organization's goals. In this study using 5 leadership styles that will find out the relationship with employee discipline, namely autocratic leadership style, paternalistic style, charismatic style, Laissez Faire style and democratic leadership style. The method used in this study is a qualitative approach research method. Based on the analysis of the Leadership Style on the Leadership of the Manekar District Head, Tambrauw Regency, it can be concluded that the Democratic leadership style has been implemented well, while the Laissez Faire (free control) style in practice is only to test how much ability and responsibility is given to his subordinates. . The authoritarian leadership style is defined as obedience to the leader as a relationship between superiors and subordinates. For employee work discipline, based on indicators: punctuality discipline, discipline in using office equipment properly, high responsibility discipline, and discipline towards office rules, it can be concluded that employees who work at the Manekar District Office, Tambrauw Regency, West Papua Province can run and implement good work discipline.